Selection of surgical technique for retinal detachment with coloboma of the choroid - Jalali Subhadra; Das Taraprasad (Indian Journal of Ophthalmology, 1994)
Four eyes with rhegmatogenous retinal detachment and coloboma of the choroid were managed by conventional scleral buckling (one eye); scleral buckling combined with lensectomy, vitrectomy, and fluid-air exchange (two eyes); and vitrectomy, silicone oil injection without scleral buckling (one eye). Retinal break was seen within the coloboma in two eyes, at the periphery in one eye, and, both in the coloboma and periphery in one eye. At a follow-up of 15 months, the retina was found attached in all the patients. The success of these surgical procedures could be attributed to careful preoperative/intraoperative fundus examination and individualised surgical planning